Bertahan Melawan Stigmatisasi: Eksistensi Loenpia Gang Lombok Pecinan Kota Semarang - Rafi Akmal Rabbani; Muhammad Irsyad Khairan Amir; Rafael Aurelius Kristiano; Fauzan Syahru Ramadhan (FIHROS: Jurnal Sejarah dan Budaya, 2025)
This article focuses on examining how Loenpia Gang Lombok has been able to survive racial stigmatisation against the Chinese community, particularly at Semarang in relation to their cuisine, namely lumpia, by taking a case study of the Loenpia Gang Lombok stall. The objective of this research is to explore the social resilience of the Loenpia Gang Lombok stall in countering racial stigmatisation, particularly the stigmatisation that has become an issue or source of concern for Loenpia Gang Lombok and the Chinese community in Semarang. This study uses observational and historical methods, including heuristics, criticism, interpretation, and historiography, to analyse the development of Loenpia Gang Lombok and its social resilience. The results of this study reveal that the stigmatisation stems from societal assumptions or perceptions that the ingredients used in making Loenpia Gang Lombok contain non-halal components. However, in fact, Loenpia Gang Lombok does not use such non-halal ingredients as stigmatised by the community. The social resilience of Loenpia Gang Lombok can be analysed through various aspects, including historical perspectives, development, the stigmatisation that has occurred, and efforts to survive in the face of such stigmatisation.